Management and clinical outcomes of follicular lymphoma across continuous lines of treatments: a retrospective analysis in China - Liu, Jiaxin; Hu, Yunfei; Zhao, Linjun; Nuersulitan, Reyizha; Liu, Yanfei; Yu, Hui; Ye, Yingying; Wang, Dedao; Tang, Yongjing; Feng, Feier; Liu, Weiping; Zhu, Jun; et al. (Frontiers in Oncology, 2023)
Background Follicular lymphoma (FL) is characterized by an incurable course that frequently necessitates multiple lines of treatment. While a range of new approaches have broadened therapeutic options for patients in later lines, data regarding treatment patterns and outcomes of Chinese patients with relapsed/refractory(R/R) FL was scarcely reported. Methods This retrospective single-center study included patients diagnosed with FL grades 1–3a at our institution between January 2002 and December 2019. Endpoints of interest were analyzed according to lines and types of interventions. The endpoints mainly included overall response rate (ORR), progression-free survival (PFS), and overall survival (OS). Results The study enrolled 566 biopsy-proven patients. Among them, 544 patients initiated the first line of treatment, followed by 240 initiating the second line, 146 initiating the third line, 88 initiating the fourth line, 47 initiating the fifth line, and 28 initiating the sixth line. In terms of treatment patterns, anti-CD20 chemotherapy was a major modality in the first and second lines. However, for patients in the third line and subsequent lines, treatment approaches were diverse, and participation in clinical trials for new medications was common, which correlated with a survival benefit. The study also revealed that clinical indicators (such as ORR, PFS, and OS) gradually decreased with each subsequent line of treatment. The ORR at the first line was 86.6%, but decreased to 48.6% at the third line and 40.4% at the sixth line, respectively. Similarly, median OS and PFS decreased to 88.8 and 7.1 months at the third line and further reduced to 21.7 and 2.8 months at the sixth line, respectively. A total of 133 patients developed progression within 24 months from the initiation of first line anti-CD20 chemotherapy (POD24), and these patients exhibited poorer response rates and outcomes in subsequent lines of therapycompared to the non-POD24 group. Conclusion This study revealed the clinical routine practices and prognosis of R/R FL patients within the Chinese population. It underscored the unmet need for optimal strategies to improve survival and also served as a benchmark for future trials.